Identification and characterization of endophytic fungi isolated from Ixora chinensis as potent source of antibacterial and anticancer agents - Quach, Ngoc Tung; Nguyen, Mau Hung; Ho, Ngoc Anh; Doan, Thi Nhung; Hoang, Ha; Chu, Hoang Ha (Vietnam Journal of Biotechnology, 2025)
Endophytic fungi isolated from medicinal plants are known as prolific sources of bioactive compounds for medicinal exploitation. The present study focused on the evaluation of the distribution of fungal endophytes from Ixora chinensis collected in Ba Vi National Park and their antibacterial and anticancer activities. A total of 14 endophytic fungi were isolated from I. chinensis, among them, the highest number of endophytic fungal isolates were found in leaves (28.6%), followed by branches (21.4%), roots (21.4%), flowers (14.3%), and stems (14.3%). A combination of ITS gene sequence and morphological analysis indicates that they belonged to 8 genera, including Phyllosticta, Diaporthe, Neopestalotiopsis, Botryosphaeria, Pestalotiopsis, Lasiodiplodia, Talaromyces, and Colletotrichum. Among them, Diaporthe tectonae IBV6R1 was found to show the strongest inhibitory effect on A549 cells with the percentage inhibition of 71.8 ± 2.3% and antibacterial activity against Pseudomonas aeruginosa ATCC 9027, Escherichia coli ATCC 11105, and Staphylococcus aureus ATCC 25923 with the inhibition zones ranging from 1.5 - 21.6 mm. Further analysis also revealed that D. tectonae IBV6R1 produced 115.6 μg/L camptothecin using HPLC analysis. This is the report demonstrating the antibacterial and anticancer properties of D. tectonae. These findings recommend that D. tectonae IBV6R1 may aid in the development of novel compounds and fungal camptothecin. Future investigations are required to purify and elucidate antibacterial compounds as well as optimize camptothecin productivity.